How to be a presentation god : build, design, and deliver presentations that dominate! - Schwertly, Scott (Hoboken, NJ : Wiley, 2011)
"You'll find proven and effective step-by-step secrets for delivering transcendent presentations with an easy-to- implement approach focused on engaging content, personal storytelling, and effective design elements" -- Book jacket.
Includes index.
Keywords: Business presentations